A dataset of Zostera marina and Zostera noltei structure and functioning in four sites along the French coast over a period of 18 months - Lacoste, Elise; Ouisse, Vincent; Desroy, Nicolas; Allano, Lionel; Auby, Isabelle; Bajjouk, Touria; Bourdier, Constance; Caisey, Xavier; De Casamajor, Marie-Noelle; Cimiterra, Nicolas; Cordier, Céline; Curd, Amélia; et al. (Peer Community Journal, 2024)

(untitled)
This manuscript describes the methodology associated with the dataset entitled: A dataset of Zostera marina and Zostera noltei structure and functioning in four sites along the French coast over a period of 18 months. The data concerns the structure and morphometry of the seagrasses Zostera marina and Zostera noltei, the diversity of the associated epifauna and the benthic fluxes of oxygen, carbon and nutrients. The dataset includes 103 sampling events divided among four sites and spread across three distinct marine biogeographic regions (i.e. the English Channel, Bay of Biscay and Western Mediterranean), and up to five seasons, depending on the site. The sampling scale allows inter-site and intra-habitat comparisons. Environmental conditions are also described at the site scale. As the most comprehensive and broadscale French dataset on seagrass structure and functioning  to date, it is useful for both data analysis and management actions.